Effects of new hightech-swim-suits on passive drag - Keul, S.; Bieder, A.; Wahl, P. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Which influence do Hightech-Swim-Suits have on swimming performance was the main question during the Olympic Games 2008 and World Championships 2009. Therefore the purpose of the present study was to investigate the effects of new generation Hightech-Swim-Suits compared to conventional swimwear on passive drag. METHODS: Eight national league swimmers (4 male, 4 female) participated on repeated gliding-tests with a Semi Tethered Machine (STM). The participators wore either conventional swimwear, shoulderto- ankle Speedo LZR Racer, bluesenventy nero comp or Arena R-Evolution. For each condition athletes were towed in a 50m pool three times at water surface (s) and 0,5m deep (uw) in randomised order. Thereby velocity was measured. After smoothing the velocity-curves the means of steady state velocity were compared with ANOVA repeated measures with Fisher post-hoc test (p<0.05). RESULTS: Under both conditions (s and uw) swimsuits reached higher velocities compared to conventional swimwear. Thereby Speedo LZR always reached the highest velocities (s: 1,95ms-1 ± 0,01; uw: 2,14 ms-1± 0,01), followed by blueseventy (s: 1,91 ms-1 ± 0,01; uw: 2,10 ms-1 ± 0,01) and Arena (s: 1,91 ms-1± 0,01; 2,09 ms-1± 0,01). The lowest speeds were reached with conventional swimwear (1,87 ms-1± 0,01; 2,02 ms-1± 0,01). Significantly higher velocities at the surface were found for Speedo LZR compared to normal swimwear and Arena R-Evolution. Under water blueseventy and Speedo achieved significantly higher velocities compared to normal swimwear. DISCUSSION: Drag is an important phenomenon, because its reduction improves swimming speed. Passive drag is smaller than active drag. Anyway measuring passive drag allows exposing the effects of swimsuits without any influence of swimmers skills. Former studies measured the effects of "previous" swimsuits on active and passive drag and found different results. The present study showed advantages in wearing one of the tested suits while gliding through water. Even if the results cannot be transferred to a real situation of swimming, it can be expected, that long gliding phases under water after turns and wearing a swimsuit might improve swimming performance.